Exploratory Analysis of Racial/Ethnic and Educational Differences in a Randomized Controlled Trial of a Mindfulness-Based Weight Loss Intervention. Issue 6 (July 2021) - Daubenmier, Jennifer; Chao, Maria T.; Hartogensis, Wendy; Liu, Rhianon; Moran, Patricia J.; Acree, Michael C.; Kristeller, Jean; Epel, Elissa S.; Hecht, Frederick M.
ABSTRACT: Objective: People of color and lower socioeconomic groups have higher obesity prevalence, lose less weight compared with Whites and higher socioeconomic groups, and are underrepresented in randomized controlled trials of mindfulness-based interventions. We examined whether mindfulness approaches reduce disparities in weight loss interventions. Methods: We analyzed data from a randomized controlled trial of 194 participants with obesity (41% participants of color, 36% without college degree) comparing a 5.5-month mindfulness-based weight loss intervention to an active-control with identical diet-exercise guidelines. We assessed attendance, 18-month attrition, and weight change at 6, 12, and 18 months by race/ethnicity and education level using linear mixed models, adjusting for baseline body mass index, age, and education or race/ethnicity, respectively. Results: Participants without versus with a college degree attended fewer sessions and had higher attrition across interventions. Participants of color attended fewer intervention sessions in the mindfulness compared with the control intervention. Overall, participants of color lost significantly less weight at 12 and 18 months compared with Whites. However, during the 6- to 18-month maintenance period, we found an interaction of intervention arm, race/ethnicity, and time ( p = .035), indicating that participants of color compared with Whites regained more weight in the control (0.33 kg/mo; p = .005) but not mindfulness intervention (0.06 kg/mo; p = .62). Participants without a college degree had greater initial weight loss in the mindfulness compared to control intervention from 0 to 6 months (−0.46 kg/mo; p = .039). Conclusions: Although disparities persist, mindfulness approaches may mitigate some racial/ethnic and socioeconomic differences in weight loss compared with conventional diet-exercise programs. Trial Registration : Clinicaltrials.gov registration: NCT00960414 Abstract : Supplemental digital content is available in the text.